Comparison of general vs spinal anesthesia for direct anterior approach total hip arthroplasty in elderly patients: A retrospective study (Annals of Medical Research, 2023)
Aim: It remains unclear whether spinal anesthesia is beneficial instead of general anesthesia in total hip arthroplasty (THA) performed via the direct anterior approach (DAA) in elderly patients. The aim of the present research was to investigate the safety and effectiveness of SA in elderly patients underwent DAA-THA.Materials and Methods: We made a retrospective analysis of 166 elderly patients underwent DAA-THA between January 2018 and December 2021. Patients were divided into two groups: general anesthesia (group GA, n=88) and spinal anesthesia (group SA, n=78). We compared the two groups regarding to 90-day readmission rate, amount of bleeding, blood product transfusion, length of hospital stays (LOS), major adverse cardiac events (MACE), postoperative pulmonary complications (PPC), and intensive care unit (ICU) requirement. We also recorded the demographics and procedure data of the two groups.Results: Ninety-day readmission rate, PPC, and ICU requirement in group SA were significantly lower than group GA (p